The role of sports investment and marketing in raising the level of administrative and technical efficiency of Iraqi sports clubs - Ali, Marwa; Rahim , Haider (Journal of Physical Education, 2025)
The research aims to: build a scale for investment and sports marketing for Iraqi sports clubs, and to identify the role of investment and sports marketing for Iraqi sports clubs from the point of view of members of the administrative bodies. The researchers used the descriptive approach with the survey method to suit the nature of the problem. The research community was represented by members of the administrative bodies of the clubs of Baghdad Governorate, while the research sample was represented by (25) clubs with a number of members (200) members of the administrative body. The sample was divided into several samples: the exploratory experiment sample (10) members, the construction sample (100) members, and the application sample (90) members. A number of phrases were formulated, numbering (25) phrases, and they were presented to a group of experts. After applying the scientific foundations, the scale became composed of (25) phrases, as no phrase was deleted. Then the final image of the scale was applied to the research sample. The researchers concluded that they had reached the construction of a scale for entrepreneurial creativity at the Iraqi National Olympic Committee. The scale proved its validity for measuring creativity, investment and marketing for Iraqi sports clubs, and the possibility of applying the scale for investment and sports marketing to other samples. The research sample acknowledges that investment and sports marketing has a major role in raising the efficiency of Iraqi sports clubs.